НЕМИС ҲӘМ ҚАРАҚАЛПАҚ ТИЛЛЕРИНДЕ МОДАЛ СӨЗЛЕР - Ихласов, У.; Ихласов, И. (SCIENCE and SOCIETY, 2018)
The article is devoted to the study of modal words in the German and Karakalpak languages in the comparative aspect. The authors study the semantic peculiarities of modal words on the basis of concrete examples. In the result of the investigation there were defined the common and distinguishing features of modal words in two comporing languages.